Responsibility of Ad Hoc Judges in Deciding Cases of Gross Violations Human Rights Based on The Principles of Justice - Aryesam, Primus (Journal of The Community Development in Asia, 2023)
The research aims to; Finding the substantive responsibility of ad hoc judges in deciding cases of gross violations of human rights based on the principle of distributive justice according to Aristotle. Find personal arrangements for the procedural responsibilities of ad hoc judges according to the provisions of Indonesian legislation. Evaluating administrative responsibilities through oversight mechanisms conducted on ad hoc human rights judges. Normative juridical methods are used in research. The results of the study that ad hoc judges decide cases of gross violations of human rights do not consider the legal elements of gross violations of human rights.    The evidentiary procedure is weak because ad hoc judges are institutionally independent and personally not because the influence of the chief justice is still there. Bawasmari's internal oversight is inadequate as the judge's disciplinary examination is not transparent. This research aims to 1) Find the substantive responsibilities of ad hoc judges in deciding cases of gross violations of human rights (HAM) based on the principle of distributive justice according to Aristotle. 2) Find the regulation of procedural responsibility of ad hoc judges personally according to the provisions of legislation in Indonesia. 3) Evaluate the admi nistrative responsibility through the supervision mechanism carried out on ad hoc judges, more specifically judges in human rights courts. This research method uses a normative juridical approach or an approach that examines the law as a rule, also called doctrinal legal research, because this research is conducted or aimed at written regulations.The results showed that the responsibility of ad hoc judges in deciding cases of gross violations of human rights should use the elements of the law of gross violations of human rights (HAM) but the fact that it is ruled out means that the judge's decision is considered unfair because it does not comply with existing legal standards, as well as the responsibility of judges in applying the evidentiary system in the legal process is weak. It was also found that the procedures for resolving gross violations of human rights have been implemented, but currently judges are institutionally independent and personally not so, therefore their decisions are certainly not fully independent, because they are influenced by many factors such as the influence of the head of the court or other issues from outside the judge. The internal supervision mechanism by the Supervisory Board of the Supreme Court of the Republic of Indonesia is still considered half-hearted because the quality and integrity of supervision is inadequate, as seen in the process of disciplinary examination of judges that is not transparent.